Translating Planetary Health Principles Into Sustainable Primary Care Services - Gonzalez-Holguera, Julia; Gaille, Marie; del Rio Carral, Maria; Steinberger, Julia; Marti, Joachim; Bühler, Nolwenn; Kaufmann, Alain; Chiapperino, Luca; Vicedo-Cabrera, Ana Maria; Schwarz, Joelle; Depoux, Anneliese; Panese, Francesco; et al. (Frontiers in Public Health, 2022)
Global anthropogenic environmental degradations such as climate change are increasingly recognized as critical public health issues, on which human beings should urgently act in order to preserve sustainable conditions of living on Earth. “Planetary Health” is a breakthrough concept and emerging research field based on the recognition of the interdependent relationships between living organisms – both human and non-human – and their ecosystems. In that regards, there have been numerous calls by healthcare professionals for a greater recognition and adoption of Planetary Health perspective. At the same time, current Western healthcare systems are facing their limits when it comes to providing affordable, equitable and sustainable healthcare services. Furthermore, while hospital-centrism remains the dominant model of Western health systems, primary care and public health continue to be largely undervalued by policy makers. While healthcare services will have to adapt to the sanitary impacts of environmental degradations, they should also ambition to accompany and accelerate the societal transformations required to re-inscribe the functioning of human societies within planetary boundaries. The entire health system requires profound transformations to achieve this, with obviously a key role for public health. But we argue that the first line of care represented by primary care might also have an important role to play, with its holistic, interdisciplinary and longitudinal approach to patients, strongly grounded in their living environments and communities. This will require however to redefine the roles, activities and organization of primary care actors to better integrate socio-environmental determinants of health, strengthen interprofessional collaborations, including non-medical collaborations and more generally develop new, environmentally-centered models of care. Furthermore, a planetary health perspective translated in primary care will require the strengthening of synergies between institutions and actors in the field of health and sustainability.